Optimalisasi Program Sekolah Ramah Anak Melalui Kampanye Anti Bullying di SMP Negeri 2 Gamping - Dwi Eka Kartika Sari; Loisa Desti Salma; Wilda Rumaysa Salam; Nadia Nur Addina; Pena Sejuk Samudera Biru; Gerry Katon Mahendra; Erni Saharuddin (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
One of the government's strategic policies for fostering a safe, comfortable learning environment free from violence including bullying is the Child-Friendly School (CFS) initiative. This community engagement project took place at SMP Negeri 2 Gamping and aimed to support a more effective rollout of the CFS program through an anti-bullying awareness campaign. Two main approaches were applied: in-depth interviews with a Guidance and Counseling (BK) teacher, and outreach sessions involving 10 students drawn from class VII A, which has 32 students in total. The interview with the BK teacher centered on how far the CFS program had progressed, particularly regarding interactive classroom instruction, the history of reported bullying incidents, handling approaches used, persistent forms of bullying, and ongoing communication gaps between teachers and students. The project ran across a one-week period, starting with submission of a permission letter on Monday, followed by outreach activities and interviews on Thursday. Findings indicated that the CFS program had not been fully realized at the school, with gaps especially evident in interactive learning, unresolved bullying cases, and continuing communication obstacles between students and teachers. Following the anti-bullying outreach sessions, students demonstrated greater awareness of bullying types, their harmful effects, and ways to prevent them within the school setting.